2021
DOI: 10.1186/s13256-021-02701-z
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous primary pneumomediastinum: is it always benign?

Abstract: Background Spontaneous Pneumomediastinum is a rare disease. It could be a simple and self-limited condition or be a life-threatening complication of underlying diseases. The therapeutic options also differ by the cause. This systematic review was done to provide, as far as we know, the first attempt to broadly assess the clinical feature, predisposing factors, possible management, and outcome of spontaneous primary pneumomediastinum. Methods In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 14 publications
2
30
0
2
Order By: Relevance
“…[15] In instances where pneumomediastinum, pneumothorax, perforated bowel or esophageal rupture have occurred, the proposed pathophysiology for development of PNR is tracking of air through the neural foramina into the spinal canal. [1,3] ere are no pathognomonic signs or symptoms associated with PNR. ere have been cases reported with neurological symptoms in the setting of iatrogenic and traumatic PNR secondary to cord compression.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[15] In instances where pneumomediastinum, pneumothorax, perforated bowel or esophageal rupture have occurred, the proposed pathophysiology for development of PNR is tracking of air through the neural foramina into the spinal canal. [1,3] ere are no pathognomonic signs or symptoms associated with PNR. ere have been cases reported with neurological symptoms in the setting of iatrogenic and traumatic PNR secondary to cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 systematic review of the literature by Alemu et al that examined 339 pediatric and adult cases of spontaneous pneumomediastinum found PNR in 2.06% of cases. [1] In children, the incidence of PNR in a population of pediatric patients with spontaneous pneumomediastinum has been reported as high as 10%. [7] In our review of the literature for cases of truly spontaneous PNR without predisposing acute or chronic conditions (such as acute respiratory illness or asthma), we found that the location of the air most commonly found in the cervicothoracic spine, with the cervical spine, alone as the next most common location e predilection for the cervical spine has an anatomical explanation; there is no fascial barrier between the posterior mediastinum and the cervical epidural space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations